2003
DOI: 10.1039/b212160n
|View full text |Cite
|
Sign up to set email alerts
|

The levelling effect of solvational imbalances in the reactions of oximate α-nucleophiles with electrophilic phosphorus centers. Relevance to detoxification of organophosphorus esters

Abstract: A study of the reactions of oximate alpha-nucleophiles with diisopropylphosphorofluoridate (DFP) and two model phosphonates, has revealed either a levelling-off in reactivity or a bell-shaped behaviour in accordance with a critical decoupling of desolvation and bond formation (solvational imbalances); the relevance of these results to detoxification is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…More recently, we showed that fenitrothion degradation was catalyzed by alkali metal ethoxides in ethanol (4). The ethanolysis was shown to proceed via three different routes (Scheme 1): (1) attack at the phosphorus center; (2) attack at the aliphatic carbon of the methoxy group; and (3) attack at the C-1 position of the aromatic ring. However, at higher concentrations of catalyst, we reported a regioselectivity in attack at the phosphorus center.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, we showed that fenitrothion degradation was catalyzed by alkali metal ethoxides in ethanol (4). The ethanolysis was shown to proceed via three different routes (Scheme 1): (1) attack at the phosphorus center; (2) attack at the aliphatic carbon of the methoxy group; and (3) attack at the C-1 position of the aromatic ring. However, at higher concentrations of catalyst, we reported a regioselectivity in attack at the phosphorus center.…”
Section: Introductionmentioning
confidence: 98%
“…We and others have previously studied nucleophilic catalysis and degradation pathways of organophosphorus esters including OP pesticides. [18][19][20][21][22][23] Importantly, both types of processes, H/D exchange and nucleophile catalysis, involve coordination of a metal ion into a Lewis base site (N, O, S) in the heterocyclic residue and ester moiety, respectively.…”
mentioning
confidence: 99%
“…This route enables convenient access to isotopically labelled product [4-13 C] (34) from commercially available [1-13 C]-2-propionic acid. 18 A novel and practical synthesis of S-(1-and 2-halogenoalkyl) sugars (43), including some at the anomeric center, has been developed. The 7-allyl compound ( mammalian protein-farnesyl transferase, but surprisingly the other analogues are effective alternative substrates for this enzyme (Figure 7).…”
Section: Phosphoric Acids and Their Derivativesmentioning
confidence: 99%
“…2 Â 10 3 times more reactive toward ion-paired EtO À Li 1 in anhydrous EtOH (Scheme 15). 43 A detailed study of the specific rates of solvolysis of N,N,N 0 ,N 0 -tetramethyldiamidophosphorochloridate (80) (TMDAPC) with analysis in terms of the extended Grunwald-Winstein equation has been reported (Scheme 19). 41 The same authors proposed catalytic methanolysis promoted by La 31 as a new method for controlled decomposition of paraoxon (74) (Scheme 17).…”
Section: Scheme 13mentioning
confidence: 99%